2023
DOI: 10.3390/coatings13071244
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Influence Law of Ce on Microstructure and High-Temperature Oxidation Resistance of Ti-Al-Si Composite Coating

Abstract: High-temperature titanium alloys are widely used in aerospace hot parts; however, the thermal barrier temperature of 600 °C limits its service temperature. In this paper, a two-step hot-dip plating method is proposed to prepare the composite coating containing Ce on the surface of titanium alloy, which can make the oxidation resistance temperature of titanium alloy reach 800 °C The microstructure, phase composition, and element distribution of Ce-containing Ti-Al-Si hot-dip coating, Ce-containing Ti-Al-Si pre-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Many studies have shown that a moderate number of rare-earth elements can improve the high-temperature oxidation resistance of titanium alloys. To improve the hightemperature oxidation resistance of Ti65 alloy, Zeng Siqi et al [45] prepared a Ti-Al-Si composite coating with Ce added on the surface of Ti65 alloy using a two-step hot-dipping method. The main components of the coating were (Ti,Ce)(Al,Si) 3 phases.…”
Section: Rare-earth-modified Aluminide Coatingmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have shown that a moderate number of rare-earth elements can improve the high-temperature oxidation resistance of titanium alloys. To improve the hightemperature oxidation resistance of Ti65 alloy, Zeng Siqi et al [45] prepared a Ti-Al-Si composite coating with Ce added on the surface of Ti65 alloy using a two-step hot-dipping method. The main components of the coating were (Ti,Ce)(Al,Si) 3 phases.…”
Section: Rare-earth-modified Aluminide Coatingmentioning
confidence: 99%
“…It promoted the formation of continuous Al 2 O 3 and prevented crack propagation, thus improving the high-temperature oxidation resistance of Ti65 alloy [45].…”
Section: Cementioning
confidence: 99%